New Insights into the Phage Genetic Switch: Effects of Bacteriophage Lambda Operator Mutations on DNA Looping and Regulation of PR, PL, and PRM. Issue 22 (6th November 2016) - Lewis, Dale E.A.; Gussin, Gary N.; Adhya, Sankar
Abstract: One of the best understood systems in genetic regulatory biology is the so-called "genetic switch" that determines the choice the phage-encoded CI repressor binds cooperatively to tripartite operators, O L and O R, in a defined pattern, thus blocking the transcription at two lytic promoters, P L and P R, and auto-regulating the promoter, P RM, which directs CI synthesis by the prophage. Fine-tuning of the maintenance of lysogeny is facilitated by interactions between CI dimers bound to O R and O L through the formation of a loop by the intervening DNA segment. By using a purified in vitro transcription system, we have genetically dissected the roles of individual operator sites in the formation of the DNA loop and thus have gained several new and unexpected insights into the system. First, although both O R and O L are tripartite, the presence of only a single active CI binding site in one of the two operators is sufficient for DNA loop formation. Second, in P L, unlike in P R, the promoter distal operator site, O L 3, is sufficient to directly repress P L . Third, DNA looping mediated by the formation of CI octamers arising through the interaction of pairs of dimers bound to adjacent operator sites in O R and O L does not require O R and O L to be aligned "in register", that is, CI bound to "out-of-register" sub-operators, for example, O L 1 ~  O l 2 and O R 2 ~  O R 3, can also mediate loop formation. Finally, based on an examination of the mechanism of activation of P RM when only O R 1 or O R 2 are wild type, we hypothesize that RNA polymerase bound at P R interferes with DNA loop formation. Thus, the formation of DNA loops involves potential interactions between proteins bound at numerous cis -acting sites, which therefore very subtly contribute to the regulation of the "switch". Graphical Abstract: In vitro analysis of Bacteriophage lambda's maintenance of the lysogenic state has revealed new insights into the mechanisms by which a DNA looping of a segment of lambda DNA participates in the lysogenic maintenance. Highlights: New insights into the mechanisms of Bacteriophage lambda's maintenance of the lysogenic state DNA looping by CI repressor in prophage maintenance Mechanisms of DNA looping